It's B
Slope is negative, the other must be positive due to m1 x m2 = - 1
m1 = -2/5
The diagram shows a gradient of -2/5. So, the
reciprocal of this valve to make - 1 is 5/2 (which is the - 2/5 flipped upside down, but positive)
-2/5 x 5/2 = - 10/10 (or - 1)
Thus, the perpendicular line to this has a gradient of 5/2.
Hope this helps!
Answer:
A)
Step-by-step explanation:
length = x +x + 2 = 2x + 2
Width = 2+ x
Area of rectangle = length *width
(x +2)(2x + 2) = 110
Use FOIL method
x*2x + x*2 + 2*2x + 2*2 = 110
2x² + <u>2x + 4x</u> + <u>4 - 110</u> = 0 {Combine like terms}
2x² +6x - 106 = 0
a = 2 ; b = 6 ; c = -106
b² - 4ac = 6² - 4*2*(-106)
= 36 + 848
= 884
![\sqrt{b^{2}-4ac}=\sqrt{884}= 29.73](https://tex.z-dn.net/?f=%5Csqrt%7Bb%5E%7B2%7D-4ac%7D%3D%5Csqrt%7B884%7D%3D%2029.73)
![x =\dfrac{-b+\sqrt{b^{2}-4ac}}{2a} \ ; \ x==\dfrac{-b-\sqrt{b^{2}-4ac}}{2a}\\\\x = \dfrac{-6+29.73}{2*2} \ ; \ x =\dfrac{-6-29.73}{2*2} \ this \ is \ ignored \ as \ it \ is \ negative\\\\x=\dfrac{23.73}{4};](https://tex.z-dn.net/?f=x%20%3D%5Cdfrac%7B-b%2B%5Csqrt%7Bb%5E%7B2%7D-4ac%7D%7D%7B2a%7D%20%5C%20%3B%20%5C%20x%3D%3D%5Cdfrac%7B-b-%5Csqrt%7Bb%5E%7B2%7D-4ac%7D%7D%7B2a%7D%5C%5C%5C%5Cx%20%3D%20%5Cdfrac%7B-6%2B29.73%7D%7B2%2A2%7D%20%5C%20%3B%20%5C%20x%20%3D%5Cdfrac%7B-6-29.73%7D%7B2%2A2%7D%20%5C%20this%20%5C%20is%20%5C%20%20ignored%20%5C%20as%20%5C%20it%20%5C%20is%20%5C%20%20negative%5C%5C%5C%5Cx%3D%5Cdfrac%7B23.73%7D%7B4%7D%3B)
x = 5.93 m
Answer:
-1/5
Step-by-step explanation:
Perpendicular lines have slopes that are the opposite reciprocal of one another.
The slope of line t is the opposite reciprocal of the slope of line s:
slope of t = -1/(slope of s)
slope of t = -1/5
The exact
value of the given equation is 45 degrees or pi/4. I am hoping
that this answer has satisfied your query about and it will be able to help
you, and if you’d like, feel free to ask another question.
Answer:
$196
Step-by-step explanation:
Lets assume,
cost of a belt = 'x'
cost of a pair of pants = 'y'
Now, According to the question;
- x + y = 490;
- cost of a bag = twice the cost of belt = 2x;
- cost of a pair of pants = twice the cost of bag
⇒ y = 2×2x ⇔ 4x
hence, by subtituting the values in equation' we get;
⇒ x + 4x = 490
⇒ 5x = 490
⇒ x = 98
So, the difference between the cost of the pair of pants and the bag ;
⇒ y - 2x
⇒ 4x - 2x
⇒ 2x = 2×98 = 196.